Badania postaw twórczych uczniów w procesie poznawania lektury szkolnej (uwagi metodologiczne) = Researches about Creative Attitudes of Pupils in the Process of Comprehension of School Reading (Methodical Notes) - Biłos, Edward (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In this review the author attempts to give a theoretical and empirical meaning to the concept creative attitudes of pupils in the process of school-reading comprehension, an attempt, which he dennes as an pupils-organized system of action. These actions create the tendency towards an unconventional behavior in a positive sense on the base of the autonomy of the pupil as an individual and on the base of his acknowledged values and trend of performance
Keywords: uczniowie; badania; szkolnictwo